2019
DOI: 10.1002/ar.24060
|View full text |Cite
|
Sign up to set email alerts
|

Is the Mole Rat Vomeronasal Organ Functional?

Abstract: The colonial naked mole rat Heterocephalus glaber is a subterranean, eusocial rodent. The H. glaber vomeronasal organ neuroepithelium (VNE) displays little postnatal growth. However, the VNE remains neuronal in contrast to some mammals that possess nonfunctional vomeronasal organ remnants, for example, catarrhine primates and some bats. Here, we describe the vomeronasal organ (VNO) microanatomy in the naked mole rat and we make preliminary observations to determine if H. glaber shares its minimal postnatal VNE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…The vomeronasal capsule consists of cartilage in most mammalian species, including carnivores [15][16][17], ungulates [19,[33][34][35], bats [31], primates [20], rabbits [27,29], elephants [21,22], hyraxes [23], armadillos [30], marsupials [24,25], and hedgehogs (revealed in the present study). However, the capsule is bony in some rodents, for example, rats, mice [27], hamsters [36], and caudal third in capybaras [37], although it is partly or mostly cartilaginous in mole rats [38]. Interestingly, the vomeronasal capsule of musk shrews also consists of bone [32], which we also confirmed [13], unlike that of the hedgehog.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The vomeronasal capsule consists of cartilage in most mammalian species, including carnivores [15][16][17], ungulates [19,[33][34][35], bats [31], primates [20], rabbits [27,29], elephants [21,22], hyraxes [23], armadillos [30], marsupials [24,25], and hedgehogs (revealed in the present study). However, the capsule is bony in some rodents, for example, rats, mice [27], hamsters [36], and caudal third in capybaras [37], although it is partly or mostly cartilaginous in mole rats [38]. Interestingly, the vomeronasal capsule of musk shrews also consists of bone [32], which we also confirmed [13], unlike that of the hedgehog.…”
Section: Discussionsupporting
confidence: 73%
“…The lumen of the VNO is round-to-oval throughout its entire length in the African pygmy hedgehog. It is also oval in common marmosets [41] and some species of mole rats [38], but is typically crescent-shaped in most mammals [3], including musk shrews [32]. The form of the duct within hedgehog VNO is more similar to that of large secretory gland ducts, and it might smooth the flow of serous gland secretions.…”
Section: Discussionmentioning
confidence: 99%
“…Not all females in a specific population reproduce every year, and the proportion of females that do not reproduce is highly variable and correlates with population density, likely due to the social suppression of reproduction in large groups (Gentle, 2005). This suppression has recently been observed in other species, such as the naked mole‐rat (Dennis et al ., 2020). The availability of food allows dominant females to subordinate sterile females, who help to raise the litter and assist with group formation (Cavallini and Santini, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Hystricognathi has become a model group for the study of the anatomical diversity of the VNS, as shown by the studies in chinchillas 16 , 17 , guinea pigs 18 , degus 19 , 20 , and mole rats 21 , 22 . Suárez et al 23 paid special attention to the organisation of the first integrative centre of the VNS, the accessory olfactory bulb (AOB) in capybaras Hydrochoerus hydrochaeris , particularly to the morphometry of the anteroposterior zonation, which is determined by the expression of the G proteins.…”
Section: Introductionmentioning
confidence: 99%